Re-assessing the Development of Da'wa Science: Da'wa Study in Academic Work Discourse - Syam, Nur (Proceedings of International Conference on Da'wa and Communication, 2019)
Lecturer Resources at the Faculty of da'wa and Communication are sufficient. There are many lecturers who hold doctoral degree with various studies. Their presence is certainly very meaningful for the development of da'wa science indeed really needs rapid development. Therefore, there are a few notes to notice. First, most studies of da'wa are within the da'wa factor paradigm, so that other paradigms such as the system paradigm, developmentalism paradigm and interpretive paradigm have not yet obtained an adequate proportion of studies. Secondly, a consortium of experts in the field of da'wa is needed in collaboration with other sciences, to discuss and develop monodisciplinary, interdisciplinary and cross-disciplinary and even multi-disciplinary studies. Thirdly, efforts are needed to write and develop studies in interdisciplinary or cross-disciplinary studies and even multidisciplinary in the science of da’wa. It can be considered, that most studies of da'wa interdisciplinary, and cross disciplinary are also immature. If it already exists (da'wa psychology, da'wa sociology and da'wa management) it is still an introductory study and has not been developed yet in a deeper direction. Moreover, interdisciplinary and cross-disciplinary studies (da'wa anthropology, da'wa political studies, da'wa law studies, etc.) have not yet been optimally developed.